An Analysis on Expropriation of Property in Indonesia Applying International Law Rules - Baskoro, Yonathan Andre; Sarjana, I Made; Kasih, Desak Putu Dewi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to evaluate and analyze the enforcement of arbitration awards and the resulting solutions in international trade and investment law. The minor remedial measures provided for therein, their nature, objectives and impact on Member States; The conclusions of this research will suggest possible changes to the settlement efforts regulated in the WTO Dispute Settlement Mechanism. This will enable member states whose trade has been severely impacted by illegal acts to rebuild their sectors and ensure the Organization's goal of protecting and promoting trade liberalization.The academic success of law has been measured within the framework of the doctrinal methodology, which includes tracking legal precedents and legislative interpretations. The doctrinal method is simply scholarship rather than a separate research methodology